Central nervous system relapse of rhabdomyosarcoma. Issue 1 (11th July 2017) - De, Brian; Kinnaman, Michael D.; Wexler, Leonard H.; Kramer, Kim; Wolden, Suzanne L.
Abstract: Purpose: The optimal management of central nervous system (CNS) relapse of rhabdomyosarcoma (RMS) is unclear. We examined diagnosis, management, and outcomes of patients with RMS developing CNS relapse. Methods: Records of 23 patients diagnosed with CNS relapse between 1999 and 2016 were reviewed. Median age at presentation of CNS relapse was 15 years (range, 1–34 years). High‐risk features at initial presentation were as follows: 16 alveolar patients, 13 Stage IV, and 13 with primary tumor in parameningeal locations. Results: CNS relapse occurred at a median 12 months (range, 1–23 months) from diagnosis and most common presenting symptoms were headache (n = 9), nausea/vomiting (n = 8), visual difficulty (n = 5), and none (n = 5). Leptomeningeal metastases were detected in 21 patients while only 2 developed parenchymal metastases without leptomeningeal involvement. Fifteen patients received CNS‐directed radiation therapy (RT), including craniospinal irradiation to a median 36 Gy (range, 18–36 Gy) and/or whole brain radiotherapy to a median 30 Gy (range, 6–41.4 Gy). Three patients received concurrent chemotherapy. Follow‐up magnetic resonance imaging was conducted in 13 patients after RT initiation with 8 demonstrating improvement, 2 with stable disease, and 3 with progression. Twelve patients were tested for reactivity to I‐131‐labeled monoclonal antibody 8H9, and three tested positive and received at least one intra‐Ommaya dose; all three lived >12 months post‐CNS relapse. Twenty‐one patients died of CNS disease and two of metastatic disease at other sites. Median survival post‐CNS relapse was 5 months (range, 0.1–49 months). Conclusions: The prognosis for patients with RMS developing CNS relapse remains poor. Treatment including CNS‐directed RT should be considered and investigation into preventative therapies is warranted.